Analysis of the influence of differences of tax rates on capital movement - PetrovaА. Yu.; Akulova, G. V.; Nazarenko , N. V. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
The work is devoted to the study of the behavior model of mobile economic agents operating in multiple jurisdictions. An experiment to change the parameters of the tax burden with the help of a multi-agent model is carried out. This model simulates the conventional game world of two jurisdictions, which are the agents of the owners of the factor of production. Initial parameters for the experiment have been created according to the author’s developments. The variable changing during the experiment from 10% to 40% – capital tax rate has been chosen. The change step is 5%. The model has been launched with five runs for the above settings. Dynamics for 24 time points is considered and average values are calculated, which enabled to smooth potential emissions in the resulting indicators. The impact of changes in the tax burden on the welfare of those agents who possess the relevant factor has been, and it is shown that the saving rate of agents of the owners of capital in the first jurisdiction affects not only the tax burden of the jurisdiction, but the tax burden is the second jurisdiction where the tax rate on income from factor capital is 25% for all the runs if you change the bet in the first jurisdiction. The obtained results coincide with the phenomena that exist in the real economy, namely in the jurisdiction with the lowest tax burden are the most attractive for the movement of their capital by owner organizations in order to increase profits. With the help of regression models we cannot only observe the effects that exist in the real economy, namely, the impact of the tax burden of one country on the welfare (in this statement – accumulation) of the economic agents of another country but also to assess the essence of this influence.